New clerodane diterpenoid from the bulbils of Dioscorea bulbifera - Kidyu K. (2014)
A new clerodane diterpenoid has been isolated from the acetone extract of bulbils of Dioscorea bulbifera. The structure of compound 1 was established as 15,16-epoxy-6α-O-acetyl-8β-hydroxy-19-nor-clero-13(16),14-diene-17, 12;18,2-diolide on the basis of comprehensive spectroscopic techniques. Dioscorea bulbifera, Dioscoreaceae, clerodane diterpenoid.